Efforts To Reduce Downgrade Of Steel Pipes In The Production Process Using The HEART Method - Irfan Widya Julianto; Hana Catur Wahyuni (Procedia of Engineering and Life Science, 2021)
Pt X is a company that produces steel pipe of various shapes and size. In the production procces not only using machines but also using humans as operators. So in this case humans play an important role in maintaining the quality of production. The purpose of this study is to analyze the human error probability with Human Error Assessment and Reduction Technique method (HEART). HEART is a method designed as a fast and simple human reliability assessment in quantifying the risk of human error. From this research, it was found that 3 tasks had a high HEP value which caused the decline in pipe quality during the production process, namely task 3.2, 4.1 and task 3.4. Which has the highest HEP value on task 3.2, namely setting the machine with a value of 0,7680. The cause is due to the lack of operator expertice and the center roll was not carried out when installing it, so that training is needed to increase operator expertice.